2018
DOI: 10.1111/are.13896
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of systemic granulomatosis is modulated by the feeding sequence and type of enrichment in meagre (Argyrosomus regius) larvae

Abstract: Systemic granulomatosis is the most frequent disease in juvenile and adult meagre, but studies regarding the first appearance of granulomas in larvae do not exist. In order to evaluate this, meagre larvae were fed four different feeding regimes as follows: RS and RO (rotifer enriched with Easy DHA Selco or Ori-Green from 3 to 30 dph respectively), RAS and RAO (rotifer enriched with Easy DHA Selco or Ori-Green from 3 to 21 dph and Artemia enriched with Easy DHA Selco or Ori-Green from 12 to 30 dph respectively)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 48 publications
2
6
1
Order By: Relevance
“…It has previously been shown that the co-feeding with rotifer and Artemia enriched with Easy DHA Selco prior to eating an inert commercial microdiet prevented the appearance of granulomas in meagre larvae (Ruiz et al, 2018b). Consistently, no granulomas were observed at 30 dph in the present trial after following the same feeding sequencing and enrichment protocol what seems to reinforce the role of nutrition as the main trigger in the appearance of systemic granulomatosis.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…It has previously been shown that the co-feeding with rotifer and Artemia enriched with Easy DHA Selco prior to eating an inert commercial microdiet prevented the appearance of granulomas in meagre larvae (Ruiz et al, 2018b). Consistently, no granulomas were observed at 30 dph in the present trial after following the same feeding sequencing and enrichment protocol what seems to reinforce the role of nutrition as the main trigger in the appearance of systemic granulomatosis.…”
Section: Discussionsupporting
confidence: 88%
“…The substitution of fish oil by krill oil was enough to the correct growth of meagre larvae but increased the percentage of granulomas and the peroxidation index. Therefore, it has been demonstrated in the present and previous studies (Ruiz et al, 2018b) that systemic granulomatosis can be completely mitigated in meagre larvae by controlling feeding sequence as well as levels of antioxidant nutrients.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations